1989
DOI: 10.1111/j.1651-2227.1989.tb11289.x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Jaundice in Infants of Diabetic Mothers

Abstract: and the 'Gerhard Katsch' Central Research Institute for Diabetes, Karlsburg, G.D.R.). Neonatal jaundice in infants of diabetic mothers. Acta Paediatr Scand Suppl360: 101, 1989. 357 IDMs and 20 healthy newborns of non-diabetic mothers were examined at term for body measurements, red blood cell count, serum bilirubin, cord blood insulin and blood glucose during the first postnatal week. The stage of maternal diabetes did not influence the course of neonatal bilirubin levels, but the IDMs had prolonged and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 7 publications
(2 reference statements)
1
6
0
Order By: Relevance
“…The asymmetric LGA infants experienced a higher frequency of severe hypoglycemia (blood glucose < 20 mg/dL) and hyperbilirubinemia, reflecting persistently elevated fetal insulin levels after delivery and increased hemolysis and delayed clearance of bilirubin. These findings are consistent with those of Ballard et al and Jährig et al 5,6 The increased risk of complications associated with asymmetric LGA infants emphasizes the need to identify these infants in utero. The asymmetric LGA growth pattern is predominantly found in offspring of diabetic mothers.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The asymmetric LGA infants experienced a higher frequency of severe hypoglycemia (blood glucose < 20 mg/dL) and hyperbilirubinemia, reflecting persistently elevated fetal insulin levels after delivery and increased hemolysis and delayed clearance of bilirubin. These findings are consistent with those of Ballard et al and Jährig et al 5,6 The increased risk of complications associated with asymmetric LGA infants emphasizes the need to identify these infants in utero. The asymmetric LGA growth pattern is predominantly found in offspring of diabetic mothers.…”
Section: Discussionsupporting
confidence: 91%
“…nemia, and acidosis than symmetric LGA (birth weight proportionate to length) infants. 5,6 Therefore, early recognition of fetuses at risk for being asymmetric LGA at birth gives the caregiver a chance to optimize management of these newborns at increased risk for morbidity and mortality.…”
mentioning
confidence: 99%
“…Peevy et al described an increased incidence of neonatal jaundice in LGA, but not AGA, infants who were born to diabetic mothers . Jährig et al found increased neonatal jaundice in AGA and LGA infants born to diabetic mothers, but noted that it was more pronounced in LGA infants . On the other hand, Gyurkovits et al studied nondiabetic macrosomic infants with birthweights of at least 4000 g and found that the incidence of neonatal jaundice was significantly lower in those infants than in the control group, where the birthweights ranged from 2500 to 3999 g. .…”
Section: Discussionmentioning
confidence: 99%
“…5 The major morbidities associated with infants of diabetic mothers include congenital malformations, macrosomia, respiratory distress syndrome, growth restriction, polycythemia, hypoglycemia, hypocalcemia, hypomagnesemia 11,12 & hyperbilirubinemia. 13 Other morbidities include myocardial dysfunction (in form of transient hypertrophic subaortic stenosis), renal vein thrombosis, and small left colon syndrome. 14 Successful management of infants of diabetic mothers is based on prevention or early recognition combined with treatment of these complications.…”
mentioning
confidence: 99%